Forest Fire Monitoring Based on Multi-Source Remote Sensing Data - Wang, Hongwei (Transactions on Environment, Energy and Earth Sciences, 2024)
Forest fires refer to forest fires that are beyond human control, freely spreading and expanding within forests, causing certain harm and losses to forests, forest ecosystems, and humans. Despite the rapid development of science in the world today, humanity has yet to make significant progress in combating forest fires. In response to the current problem of single, real-time, and comprehensive fire monitoring methods in forest fire emergency rescue work. This article explores emergency monitoring methods for forest fires based on multi-source remote sensing data. Based on comprehensive geographic data and previous scholars' specific research on remote sensing data such as drones and satellites in fire emergency monitoring, analyze the applicability, advantages, and disadvantages of various remote sensing data. The conclusion drawn is that unmanned aerial vehicle remote sensing has high spatial and temporal resolution and can implement precise fire extinguishing in small areas, while satellite remote sensing has a large spatial span and can provide information throughout the entire time period. Based on this, this article proposes a framework for emergency fire monitoring, visualizing important areas and facilities with fire development and providing information for cities and counties to extinguish forest fires.